Exploration of the chemical space of novel naphthalene-sulfonamide and anthranilic acid-based inhibitors of penicillin-binding proteins - Sosič, Izidor (Acta chimica slovenica, 2012)
Penicillin-binding proteins are a well established, validated and still a very promising target for the design and development of new antibacterial agents. Based on our previous discovery of several noncovalent small-molecule inhibitor hits for resistant PBPs we decided to additionally explore the chemical space around these compounds. In order to clarify their structure-activity relationships for PBP inhibition two new series of compounds were synthesized, characterized and evaluated biochemically: the derivatives of anthranilic acid and naphthalene-sulfonamide derivatives. The target compounds were tested for their inhibitory activities on three different transpeptidases: PBP2a from methicillin-resistant Staphylococcus aureus (MRSA) strains, PBP5fm from Enterococcus faecium strains, and PBP1b from Streptococcus pneumoniae strains. The most promising results for both of these series of compounds were obtained against the PBP2a enzyme with the IC50 values in the micromolar range. Although these results do not represent a significant breakthrough in the field of noncovalent PBP inhibitors, they do provide useful structure-activity relationship data, and thus a more solid basis for the design of potent and noncovalent inhibitors of resistant PBPs.
Keywords: anthranilic acid; antranilna kislina; inhibitorji; inhibitors; optimization; optimiziranje; penicilin; penicillin; protimikrobne učinkovine